Population Dynamics of Pests and Natural Enemies of Rice (Oryza sativa L.) Across a Karst Distance Gradient in the Bantimurung-Bulusaraung Exokarst Region, Bantimurung District, Maros Regency, South Sulawesi - Amiruddin Amin; Sylvia Sjam; Itji Diana Daud (Bogor Agricultural University, Indonesia, 2026)
Exokarst landscapes possess distinctive geomorphological and microclimatic characteristics that influence arthropod abundance and community structure in rice (Oryza sativa L.) ecosystems. Cooler and more humid microhabitats near karst formations can function as refuges that support resource stability, habitat connectivity, and trophic interactions. This study examined how distance from a karst cliff affects the abundance and composition of pest and natural enemy arthropods. Observations were conducted at three distances (0, 200, and 400 m), representing near-karst, transitional, and outer-karst microclimate zones in Kalabbirang, Bantimurung District, Maros Regency, South Sulawesi, Indonesia. A total of 1,483 individuals from 21 species were recorded. Arthropod abundance was highest at 400 m (549 individuals), followed by 0 m (477 individuals) and 200 m (457 individuals). Although total abundance was lower at 200 m, this site showed the highest species richness (S = 2.78), Shannon diversity (H′ = 2.15), and evenness (E = 0.76), indicating a more balanced community structure. Dominance was greatest at 400 m (D = 0.20), largely due to the high abundance of Coccinella sp. (205 individuals). Bactrocera dorsalis was most abundant at 0 m (125 individuals), Nephotettix virescens peaked at 200 m (106 individuals) but declined at 400 m (10 individuals), while Leptocorisa oratorius increased toward 400 m (70 individuals). Predator communities were dominated by Lycosa pseudoannulata (317 individuals). Correlation and PCA results indicate that karst-related microclimatic gradients structure arthropod communities and contribute to stronger natural pest suppression in outer-karst zones.